A SYSTEMATIC REVIEW OF TECHNOLOGY’S IMPACT ON THE TOURISM INDUSTRY - Jamalludin, Zulaffendi; Mohd Saman, Nur Rahmas; Abd Aziz, Noreen Noor (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This systematic literature review (SLR) explores the impact of technology on the tourism industry, that influence on customer interactions, operational strategies, and sustainability. Rapid technological advancements have reshaped the industry, creating both opportunities and challenges in adapting to digital innovations. Despite extensive research on this topic, the need for a comprehensive synthesis remains to understand the broader implications of technology’s integration across tourism sectors. The review adopts a structured methodology, examining 29 (n=29) peer-reviewed studies published between 2023 and 2024 from databases such as Scopus and Web of Science. A systematic and through review of existing literature was conduct, encompassing studies, experiment and implementation of immersive virtual reality (IVR) in technology on the tourism industry based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework. The selection criteria focused on studies of Technology Integration in Tourism, Behavioural Impacts in Tourism and Sustainable Tourism Development and Psychological. However, issues such as technostress, security concerns, and uneven technological adoption persist. The analysis highlights that while technology has facilitated sustainable growth, achieving a balance between growth and environmental conservation remains complex. The review concludes that strategic management, cross-disciplinary collaboration, and effective policy implementation are essential for maximizing technology’s benefits while mitigating its negative effects. The findings offer valuable insights for academics, practitioners, and policymakers aiming to enhance tourism sector resilience and sustainability.